Knowledge, Attitude and Practice Regarding Swine Flu (H1N1) among People Accompanying Patients of a Tertiary Health Care Centre, Bhuj - Niraj Bharadva; Shreyash Mehta; Pravin Yerpude; Keerti Jogdand; Kartik Trivedi (Medsci Publications, 2018)
Background: Knowledge of causative agent, symptoms, mode of transmission and its prevention of Influenza A is necessary to know for individual protection as well as to control the spread of the disease in community. Objective: To study the awareness, attitude and practices regarding H1N1 Influenza A among the people accompanying patients of GKGH, Bhuj. Material and Methods: Cross-sectional study was conducted among people accompanying the patients of GKGH after the epidemic situation. Informed verbal consent was taken from all the participants and they were interviewed personally through pre-designed and pre-tested questionnaire to elicit information regarding awareness of Influenza A (H1N1). Data such collected was analyzed using Microsoft Excel 2007 Results: Of the 227 people included in the study, 105 (46.26%) knew that it was a viral disease. Of all the participants, 123 (54.19%) knew about the mode of transmission. Around three fourth (74.01%) participants told cough & cold as a major symptoms and 71.81% told fever as a major symptom. Less commonly occurring symptoms such as vomiting (7.93%) and diarrhoea (2.64%) were known to few participants. Conclusion: Knowledge regarding Influenza A (H1N1) needs to be enhanced among people through appropriate awareness programs to prevent spread of disease on large scale.